Development definition of strength and anaerobic abilities in jump tests: classification, methodology of measuring and norms of estimation of standing high jump - Сергієнко Леонід Прокопович, (Leonid Serhiyenko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to define the methodology of carrying out the tests: standing high jump and to systematize the general notion about measuring of strength and anaerobic human abilities. Material and Methods: methods of theoretic analysis and generalization, method of search and study of scientific information were used. Results: the standing high jump classification which helps to differentiate jumps according to the way of fulfillment and estimation of the development of motor abilities ware founded. Conclusion: the methodology of doing different kinds of jumps is described.